Outcomes of surgical interventions for primary childhood glaucoma in Northern Tanzania. Issue 2 (20th April 2016) - Fieß, Achim; Furahini, Godfrey; Bowman, Richard; Bauer, Jacqueline; Dithmar, Stefan; Philippin, Heiko
Abstract : Aim: To evaluate goniotomy, trabeculotomy, transscleral cyclophotocoagulation (TSCPC) and trabeculectomy as initial procedures in children with primary childhood glaucoma from Northern Tanzania. Methods: A retrospective analysis of consecutive interventions for primary childhood glaucoma from 2000 to 2013 was conducted at the Kilimanjaro Christian Medical Centre. Success was defined as postoperative intraocular pressure (IOP) below 22 mmHg. Success rates, IOP, visual acuity (VA), subsequent interventions and potential risk factors for failure were reported for the respective interventions. Results: The study included 116 eyes of 70 children (age 4.6±5.9 years) with primary childhood glaucoma; 46 (65.7%) children were male. The preoperative IOP was 33.1±10.2 mmHg, the preoperative cup/disc (CD) ratio 0.71±0.3 and the corneal diameter 13.3±1.4 mm. As a primary intervention, 61 (52.6%) eyes underwent goniotomy, 10 (8.6%) eyes trabeculotomy, 12 (10.3%) TSCPC and 33 (28.4%) trabeculectomy. Follow-up data after 12 months were available for 63 (54.3%) eyes. Success rates at 12 months were 38% (goniotomy), 30% (trabeculotomy), 17% (TSCPC) and 64% (trabeculectomy). All interventions achieved a statistically significant IOP reduction at 3, 6 and 12 months, except for trabeculotomy after 6 months and TSCPC at all time points. Postoperative endophthalmitis occurred in one child treated with trabeculectomy. VA in 82% of all eyes was maintained or had improved after 12 months. Conclusions: Based on the success rates of this retrospective analysis, goniotomy or trabeculotomy for younger and trabeculectomy for older children can be recommended in our setting to reduce IOP. Late presentation in combination with advanced glaucomatous damage as well as erratic postoperative follow-up and treatment were likely factors that compromised overall success rates. More efforts are necessary to detect the blinding disease earlier and improve adherence to follow-up.